THE RELATION OF SERUM OMENTIN-1 LEVEL WITH INSULIN RESISTANCE IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME AND ITS RELATION WITH METFORMIN TREATMENT (Iraqi Journal of Medical Sciences, 2018)
Background: Polycystic ovary syndrome (PCOS) is still a matter of research looking for the true pathogenesis of this enigmatic syndrome. Although the majority of cases are familial, genetic studies have failed so far to identify the specific genes involved. The presentations of PCOS are heterogeneous and may change throughout the lifespan, starting from adolescence to post-menopausal age, and may have health impaction later in life. Omentin-1 is a fat depot-specific secretory protein produced by visceral stromal vascular cells. Recent studies showed that omentin-1 is correlated inversely with obesity and insulin resistance.Objective: To assess the serum omentin-1 concentration in PCOS women and the effect of metformin on omentin-1 level, to evaluate the role of omentin-1 on insulin resistance and hyperandrogenemia in PCOS women and to look for the correlation of omentin-1 with body mass index (BMI) in PCOS women.Methods: Eighty women involved in this study; 40 women with PCOS diagnosed according to Rotterdam ESHRE/ASRMS 2003 criteria and 40 apparently healthy women considered as the control group. The participants were allocated into six groups: “10 obese women with PCOS (BMI ?30 kg/m2, without metformin treatment)”. “10 obese women with PCOS (BMI ?30 kg/m2, taking metformin)”. “10 non-obese women with PCOS (BMI
Keywords: Polycystic ovaries PCOS; omentin; hyperandrogenemia; insulin resistance